How to End a Love Story - Kuang, Yulin (New York : Avon Books, an imprint of HarperCollinsPublishers, 2024)
Two screenwriters deal with their past relationship as they work together on a new TV series.
Keywords: Women novelists -- Fiction; Grief -- Fiction; Guilt -- Fiction; Sisters -- Fiction. -- Death; Screenwriters -- Fiction; Man-woman relationships -- Fiction; Los Angeles (Calif.) -- Fiction; Romance fiction